Urban solid waste and circular economy in Pachuca, Hidalgo, Mexico - Ceballos Pérez, Sergio Gabriel; Brambila Paz, José de Jesús; Pérez Cerecedo, Verónica (Acta Universitaria, 2022)
Urban solid waste (USW) represents one of the sources of pollution that can generate harmful effects such as pests, bad odors, sources of infection, and disease transmission. Integrated waste management consists of the collection, separation, treatment, and confinement in sanitary landfills. However, the circular economy (CE) promotes the efficiency of the use of materials and energy through the 5R. The objective of this article was to know how USW management is carried out and to identify the possibility of moving towards an EC at Pachuca city. The methodology consisted of a descriptive case study, using semi-structured and directed interviews, field reconnaissance, and collection of statistical information. Results show that the generation of USW in Pachuca is one of the highest in Mexico, that the use of these residues is minimal, and that there are few recovery projects.